2018
DOI: 10.22201/cgeo.20072902e.2018.2.605
|View full text |Cite
|
Sign up to set email alerts
|

A multi-elemental study to establish the natural background and geochemical anomalies in rocks from the Sonora river upper basin, NW Mexico

Abstract: Growing industrialization, including mining activity, dramatically increases environmental pollution. Exploitation of natural resources triggers landscape alteration, inputs of potentially toxic chemical elements to the environment and health diseases. In the case of mining activity, the measure of any associated environmental disturbance requires a geochemical background as a reference frame. Since in Mexico, there is a lack of this type of references in mining districts, the present study took a recent minin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…The study area has a long history of mining activity. Thus, mine tailings, abandoned mines, active mines, as well as natural mineralization (Calmus et al, 2018;Del Rio-Salas et al, 2019;Guzmán et al, 2019) occurs in the region. The main mining operations correspond, from north to south, to the El Gachi mine (Pb-Zn) located east of Arizpe, the Santa Elena mine (Au) localized east of Banámichi, the San Felipe mine (Cu, Pb, Zn and Au), as well as, El Jaralito (W) and the Washington mine (Cu, W and Mo) situated west and east of Baviácora, respectively (Calmus et al, 2018).…”
Section: Study Site and Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…The study area has a long history of mining activity. Thus, mine tailings, abandoned mines, active mines, as well as natural mineralization (Calmus et al, 2018;Del Rio-Salas et al, 2019;Guzmán et al, 2019) occurs in the region. The main mining operations correspond, from north to south, to the El Gachi mine (Pb-Zn) located east of Arizpe, the Santa Elena mine (Au) localized east of Banámichi, the San Felipe mine (Cu, Pb, Zn and Au), as well as, El Jaralito (W) and the Washington mine (Cu, W and Mo) situated west and east of Baviácora, respectively (Calmus et al, 2018).…”
Section: Study Site and Contextmentioning
confidence: 99%
“…Thus, mine tailings, abandoned mines, active mines, as well as natural mineralization (Calmus et al, 2018;Del Rio-Salas et al, 2019;Guzmán et al, 2019) occurs in the region. The main mining operations correspond, from north to south, to the El Gachi mine (Pb-Zn) located east of Arizpe, the Santa Elena mine (Au) localized east of Banámichi, the San Felipe mine (Cu, Pb, Zn and Au), as well as, El Jaralito (W) and the Washington mine (Cu, W and Mo) situated west and east of Baviácora, respectively (Calmus et al, 2018). The El Gachi mine is currently inactive and corresponds to a distal replacement deposit related to a porphyry copper-like environment, lodged in sediments that correspond to the Early Cretaceous (Zuñiga-Hernández, 2010).…”
Section: Study Site and Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Calmus et al (2018), rocks from the area have a high content of heavy metals and, in consequence, river sediments in the area have inherited a high amount of heavy metal content from the rocks.…”
Section: Study Areamentioning
confidence: 99%
“…Afterwards, some geochemical studies have been performed trying to assess the presence of residual pollutants that may represent a risk for flora, fauna and human health in the area. Nevertheless, those studies did not get conclusive results, due to the geochemistry of the area that naturally presents high contents of heavy metals (Calmus et al 2018). Some studies have used geophysical indirect indicators as electrical conductivity and magnetic susceptibility (Ramos 2017), but it was also observed that the natural presence of some minerals with high values of these properties makes difficult to distinguish the contribution of pollutants.…”
Section: Introductionmentioning
confidence: 99%